Unmasking the Warburg Effect: Unleashing the Power of Enzyme Inhibitors for Cancer Therapy - Eduardo Angulo-Elizari; Leire Gaviria-Soteras; Irati Zubiri; Sandra Ramos-Inza; Carmen Sanmartin; Daniel Plano (MDPI AG, 2023)
The Warburg effect (or aerobic glycolysis), which was first described in 1926 by Otto Heinrich Warburg, consists of the change in glucose metabolism in cancer cells. In normal cells, glucose metabolism finalizes in the mitochondria through oxidative phosphorylation (OXPHOS) in the presence of oxygen. However, the Warburg effect describes a change in the glucose metabolism in cancer cells, consuming excess glucose and converting it into lactate independently of the presence of oxygen. During this process, a wide variety of enzymes can modify their expression and activity to contribute to the mechanism of deregulated cancer metabolism. Therefore, the modulation of enzymes regulating aerobic glycolysis is a strategy for cancer treatment. Although numerous enzymes play a role in regulating aerobic glycolysis, hexokinase 2 (HK2), pyruvate dehydrogenase kinase (PDK), pyruvate kinase (PK), and lactate dehydrogenase (LDH) are worth mentioning. Numerous modulators of these enzymes have been described in recent years. This review aims to present and group, according to their chemical structure, the most recent emerging molecules targeting the above-mentioned enzymes involved in the Warburg effect in view of the future development of cancer treatments.